Reading the Late-Romantic Lending Library: Authorship and the Anxiety of Anonymity in E. T. A. Hoffmann’s Late Work - Spoerhase, Carlos (Romanticism and Victorianism on the Net, 2010)
Combining findings from the sociology of literature, the history of the book and reading, and studies on the materiality of the text, this paper reassesses a late-Romantic ‘scene of reading’ in E. T. A. Hoffmann’s My Cousin’s Corner Window (1822). This ‘scene of reading’ presents the lending library as one of the central institutions of Romanticism and depicts anonymity as a crucial mode of Romantic authorship. Furthermore, Hoffmann’s ‘scene of reading’ focuses on the significant and problematic fact that literary communication is ‘anonymized’ by the uniform materiality of the bookbindings used in late-Romantic lending libraries and associated reading practices.